Spectrofluorimetric Method for the Estimation of Erlotinib Hydrochloride in Pure and Pharmaceutical Formulations - V. Rajesh; V. Jagathi; K. Sindhuri; G. Devala Rao (E-Journal of Chemistry)
A simple and sensitive spectrofluorimetric method has been developed for the estimation of erlotinib hydrochloride in pure and pharmaceutical dosage forms. Erlotinib hydrochloride exhibits maximum fluorescence intensity in methanol and the Beer's law was obeyed in the range of 1-5 µg/mL at an excitation wavelength (λex) of 295 nm and an emission wavelength (λem) of 339 nm. Stability studies with respect to time and temperature were also carried out. The results obtained were in good agreement with the labelled amounts of the marketed formulations. This method has been statistically evaluated and found to be accurate and precise.